2018
DOI: 10.1021/jacs.8b03696
|View full text |Cite
|
Sign up to set email alerts
|

Charge Delocalization and Bulk Electronic Conductivity in the Mixed-Valence Metal–Organic Framework Fe(1,2,3-triazolate)2(BF4)x

Abstract: Metal-organic frameworks are of interest for use in a variety of electrochemical and electronic applications, although a detailed understanding of their charge transport behavior, which is of critical importance for enhancing electronic conductivities, remains limited. Herein, we report isolation of the mixed-valence framework materials, Fe(tri)(BF) (tri = 1,2,3-triazolate; x = 0.09, 0.22, and 0.33), obtained from the stoichiometric chemical oxidation of the poorly conductive iron(II) framework Fe(tri), and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 73 publications
7
177
2
1
Order By: Relevance
“…Chemically, the dopant molecules may engage with the MOF either through outer-sphere electron transfer (i.e. redox reactivity) [22][23][24][25] or through inner-sphere reactivity. The latter involves binding of guest molecules to coordinatively unsaturated metal centers to form charge transport pathways and/or to inject charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, the dopant molecules may engage with the MOF either through outer-sphere electron transfer (i.e. redox reactivity) [22][23][24][25] or through inner-sphere reactivity. The latter involves binding of guest molecules to coordinatively unsaturated metal centers to form charge transport pathways and/or to inject charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the above work, Long and co‐workers reported on electrical conductivity tuning of the iron(II) MOF Fe(tri) 2 (tri − =1,2,3‐triazolate), through a post‐synthesis chemical oxidation to achieve a mixed‐valence state . In this case, the oxidation of the framework was obtained by a structural modification and the incorporation of the tetrafluoroborate anion (BF 4 − ) into the framework, yielding the crystalline and porous phases Fe(tri) 2 (BF 4 ) x ( x =0.09, 0.22, 0.33).…”
Section: Electrically Conducting Metal‐organic Frameworkmentioning
confidence: 98%
“…[53] Interestingly, Park et al synthesized Fe(tri) 2 (BF 4 ) x (x = 0.09, 0.22, and 0.33), and found that BF 4 À ions entered the frameworks via partially oxidizing the Fe II node to Fe III . [54] The extra BF 4À ions trigger ion transfer in framework as shown in Figure 5. In addition, the electronic conductivity of this CP was elevated to 0.3 S cm À 1 .…”
Section: Mixed-valence Metal Nodesmentioning
confidence: 99%